Waiting for an Angel: Portrait of Helon Habila as a Righter - Edebor, Solomon (Àgídìgbo: ABUAD Journal of the Humanities, 2013)
This paper examines Helon Habila's Waitingfor an Angel in the context of Niyi Osundare's thesis of "the Writer as righter ", an assertion of the role of the African writer in society. The paper discusses the qualities of Habila's novel, and how they conform largely to what Osundare believes African writers must demonstrate before they could be considered as 'righters'. For this purpose, therefore, I have deliberately adopted the Marxist Literary Criticism particularly as it nligns with the revolutionary temper Osundare proposes. The paper adopts content analysis approach in exposing the tyranny of militarism and the reactions of the inhabitants of Poverty Street